Analisis Anuitas Kredit Motor Honda Revo FI Fit - Maudhunah Almunawaroh, Nurul; Kustiawati, Dedek; Fardania, Hilda; Melinda Sulton, Nindi (Rifa'Institute, 2022)
Along with the many needs of the community for their lives, especially in motorized vehicles, many financial institutions provide credit facilities to make it easier for people who want to own a motorbike in the near future but are constrained by costs. One of the institutions that provide a credit system is Honda. Honda has launched many kinds of products, one of which is Revo FI FIT. To attract buyers, Honda provides various installment offers with loan amounts and terms. The data used in this study is secondary data in the form of qualitative data by searching documents from the Honda Cengkareng website which was updated on November 30, 2022. In this study, we will analyze whether the installment calculation is in accordance with the annuity theory or not. Based on the results of data processing by calculating the theoretical formula of compound interest and ordinary annuities, it is found that the calculation of the motorcycle loan annuity is not in accordance with the ordinary annuity theory, where the installments using the ordinary annuity theory are smaller than the installments listed on the web.